The type of exercise most beneficial for quality of life in people with atrial fibrillation: a network meta-analysis - Yang, Zhen; Qi, Xiaoting; Li, Gaopeng; Wu, Na; Qi, Bingwen; Yuan, Mengyang; Wang, Yaxin; Hu, Guangling; Yang, Qiaofang (Frontiers in Cardiovascular Medicine, 2025)
IntroductionAtrial fibrillation (AF) significantly detracts from health-related quality of life (HRQoL). Despite the promotion of exercise interventions for managing AF, the effectiveness of different exercise modalities remains to be clearly defined. This systematic review and network meta-analysis aims to evaluate the comparative effectiveness of various modes of exercise interventions on HRQoL in AF patients.MethodsA random-effect network meta-analysis was performed. We conducted comprehensive searches across multiple databases, including PubMed, Web of Science, Embase, Cochrane Library, Scopus, and Chinese databases such as CNKI, WanFang Data, and VIP. The review included only randomized controlled trials (RCTs) that investigated the effects of exercise interventions on HRQoL among individuals diagnosed with AF.ResultsThe network meta-analysis (NMA) incorporated 12 studies, of which five presented some concerns regarding risk of bias and one exhibited a high risk of bias. For total HRQoL in AF patients, aerobic exercise, and cardiac rehabilitation (CR) yielded standardised mean differences of 0.60 (95% CI: 0.02–1.13) and 0.59 (95% CI: 0.20–0.99), respectively. For the physical component of HRQoL, CR was most efficacious, demonstrating the highest Surface Under the Cumulative RAnking curve (SUCRA) value of 77%. For the mental component of HRQoL, high-intensity interval training (HIIT) was superior, with the highest SUCRA value of 90.7%.ConclusionsBoth aerobic exercise and CR effectively improve the physical and mental dimensions of HRQoL as well as overall HRQoL in patients with AF. However, for the mental component of HRQoL, HIIT was identified as the most effective intervention.